Revitalizing the Social Role of Urban Mosques: A Case Study of the Jum’at Berkah Program at Darul Falah Mosque, Makassar - Suriyani Suriyani; Kaslam Kaslam; Marhaeni Saleh; Syamsul Arif Galib (Smart Society, 2025)
In contemporary urban settings, mosques are increasingly expected to fulfill not only religious functions but also to serve as centers for community development and social integration. However, challenges in governance and inclusivity often hinder this potential. This study aims to analyze the implementation of the Jumat Berkah (Blessed Friday) program at Darul Falah Mosque, Makassar, as a participatory model for revitalizing the social role of urban mosques. A qualitative case study approach was employed, involving participatory observation, in-depth interviews, and document analysis to investigate the program's implementation, management practices, and community engagement. The program successfully engaged diverse community groups, including marginalized residents and youth, while reinforcing the mosque’s role as a socially responsive institution. Transparent governance mechanisms, consistent volunteer involvement, and effective use of digital tools were found to be key to the program’s continuity and community trust. The study demonstrates that mosque-based participatory programs can address challenges of urban social fragmentation and disengagement. The novelty of this research lies in its integration of structural functionalism theory with empirical insights from mosque-led community practices, offering a replicable model for faith-based urban social development. This study contributes to both academic and practical domains. Theoretically, it enriches the discourse on mosque-based social institutions within the framework of structural functionalism. Practically, it provides a participatory model for faith-based urban social development that can be replicated by other mosques seeking to strengthen community engagement and resilience.